Regional consistency in Lateglacial chironomid-inferred temperatures from five sites in north-west England - Lang, B; Brooks, SJ; Bedford, A; Jones, RT; Birks, HJB; Marshall, JD (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
High resolution Lateglacial ice-core records from Greenland show both millennial and centennial-scale change and have been used as a benchmark for Lateglacial climatic stratigraphy throughout the North Atlantic region and beyond In this study we assess the local reflection in north-west Europe of climatic events recognised in ice cores and identify differences in the climate signature between Greenland. UK and sites in continental Europe. This study uses chironomid-inferred temperature analysis and loss-on-ignition data from five carbonate lakes in north-west England to determine the pattern of Lateglacial climatic change and demonstrates the reproducibility of chironomid-inferred temperature reconstructions both within a catchment and from sites within a small area.At both millennial and centennial scales, our results show statistical similarities between sites, giving a clear regional signal. Chironomid assemblages pick out the rapid shifts at the major event boundaries at all sites and indicate temperatures of between 12 and 13 degrees C for the region at the beginning of Greenland Interstadial 1, a rapid fall of around 4 degrees C into the Younger Dryas and a rise of around 5 degrees C in the Early Holocene At a finer scale, four centennial cooling events are identified within the interstadial, together with an oscillation in the Early Holocene which we tentatively identify as the pre-Boreal event. The records were analysed statistically using redundancy analysis and sequence-slotting techniques. Differences in the impact of individual climatic events, demonstrate that subtle changes in the chironomid-inferred temperatures reflect the local geographical setting and morphology of the lakes; with more marked impact registered in higher altitude and more wind-exposed sites. Whilst the overall pattern of Lateglacial climate can be recognised from Greenland to central Europe, Important regional differences, that can be attributed to marine influence and, perhaps, changes in atmospheric circulation, are beginning to emerge. (C) 2009 Elsevier Ltd. All rights reserved.